Design and Optimization of Metamaterial Antenna for Enhancing Satellite Communication - P., Arsavarthini; M.B., Faheema; S., Iniya; R., Karthika (IRO Journal on Sustainable Wireless Systems, 2026)
This paper presents the design and optimization of a multi-band antenna intended for use in satellite communications. The antenna consists of a pentagonal patch multi-band antenna that uses a metamaterial of split ring resonators to enhance its electromagnetic performance. Some disadvantages associated with conventional antennas include being large, having a limited bandwidth and producing high levels of signal reflection. The performance of the antenna is effective in the C, X, and Ku satellite communication bands. The proposed SRR-based pentagonal patch antenna has a low level of reflection with S11
Keywords: Metamaterial Antenna; Split Ring Resonator (SRR); Pentagon Patch Antenna; Multiband Operation; Satellite Communication